Meal timing and frequency implications in the development and prognosis of chronic kidney disease - Costa, Nara Aline; Pereira, Amanda Gomes [UNESP]; Dorna, Mariana de Souza [UNESP]; Rodrigues, Hellen Christina Neves; Azevedo, Paula Schmidt [UNESP]; Paiva, Sergio Alberto Rupp [UNESP]; Polegato, Bertha Furlan [UNESP]; Balbi, André Luís [UNESP]; Zornoff, Leonardo Antônio Mamede [UNESP]; Ponce, Daniela [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2021)
Patients with chronic kidney disease (CKD) have a higher risk of death than the general population, the main cause being cardiovascular disease (CVD). Nutrition plays a key role in the prevention and treatment of CVD and kidney diseases. Currently, new evidence reinforces the importance of specific foods and general dietary patterns rather than isolated nutrients for cardiovascular risk. In addition, dietary patterns and healthy eating habits seem extremely relevant in decreasing risk factors. Epidemiologic and clinical intervention studies have suggested that late-night dinner and skipping breakfast are associated with an increased risk of obesity, insulin resistance, and CVD. In CKD, despite important changes in nutritional counseling in recent decades, less attention has been paid to meal timing and frequency. Therefore, the purpose of this review is to discuss the evidence of meal timing and frequency in CKD development and prognosis, presented under three main topics: risk of developing CKD, importance of dietary habits, and implications of fasting.
Keywords: Chronic kidney disease; Dietary habits; Fasting; Meal timing and frequency; Prognosis